Customer and Competitor Orientation as Drivers of New Service Development and New Product Creativity: The Role of Coupled AI Capability and Strategic Agility in Indonesian Craft SMEs - Egi Andiyana; Muhamad Arifin Maulana; Sumaryo Sumaryo; Satrias Djamaran (Transforma Jurnal Manajemen, 2026)
Digital transformation is creating new innovation opportunities for small and medium-sized enterprises (SMEs), yet the benefits of artificial intelligence (AI) depend on whether firms can connect technological capability with strategic responsiveness. This study examines the effects of customer orientation and competitor orientation on new service development and new product creativity, while also assessing the role of a higher-order construct that couples AI capability with strategic agility. A quantitative, cross-sectional survey was conducted among 196 owners or managers of craft-sector SMEs registered with the Tangerang Regency Office of Cooperatives and Micro Enterprises, Indonesia. Data were collected using a 38-item, seven-point Likert questionnaire and analyzed with partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4. The results support all eight direct hypotheses. Customer orientation positively affects new service development (? = 0.303), new product creativity (? = 0.307), and AI capability–strategic agility coupling (? = 0.489). Competitor orientation also positively affects the coupling construct (? = 0.457), new service development (? = 0.271), and new product creativity (? = 0.256). In turn, the coupling construct has substantial positive effects on new service development (? = 0.442) and new product creativity (? = 0.450). The model explains 53.2% of the variance in AI capability–strategic agility coupling and 67.7% of the variance in each innovation outcome. The study extends market orientation and dynamic capabilities perspectives by showing that customer and competitor intelligence generate stronger innovation outcomes when supported by an integrated technological and strategic capability. The findings offer actionable guidance for craft SMEs and public support institutions seeking to strengthen AI-enabled innovation and sustainable competitiveness.